Patient safety challenges in primary health care: a scoping review - Carlise Rigon Dalla Nora; Mariur Gomes Beghetto (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to identify the patient safety challenges described by health professionals in Primary Health Care. Methods: a scoping review was conducted on the LILACS, MEDLINE, IBECS, BDENF, and CINAHL databases, and on the Cochrane, SciELO, Pubmed, and Web of Science libraries in January 2019. Original articles on patient safety in the context of Primary Health Care by health professionals were included. Results: the review included 26 studies published between 2002 and 2019. Four categories resulted from the analysis: challenges of health professionals, administration challenges of health services, challenges with the patient and family, and the potential enhancing resources for patient safety. Conclusions: patient safety challenges for Primary Care professionals are multiple and complex. This study provides insight into resources to improve patient safety for health care professionals, patients, administrators, policy makers, educators, and researchers.